Estrategias para gestionar intranet´s y su incidencia en la Universidad Técnica de Babahoyo, año 2015 - Zúñiga Sánchez, Miguel Ángel (2015)
Universidad Técnica de Babahoyo is an institution of higher education with educational leadership, where professionals focused on new guidelines for higher education quality are formed. It has a wide network infrastructure where different networking products for all administrative, educational and service sector is distributed. The needs to increase and improve the use of information networks have prompted the management and monitoring of them is a major factor in the field of telecommunications, so as to maintain proper operation. This is where a tool, you provide monitoring and management of data traffic on LAN is necessary. Within this project created solutions to the various problems encountered in the systems department of the Universidad Técnica de Babahoyo, could create policies to manage the network and hardware and software IP's addressing scheme for all areas was implemented administrative, academic units, classrooms, libraries, and other departments. Monitoring tools also proved allowing display the real-time traffic nodes and deployed within the internal network at the Universidad Técnica de Babahoyo equipment. It was jointly testing quality services, providing quality and responsible users of the university network service.